Development of Thai Herbal Compress Ball Extraction Method by Using Microwave-assisted Extraction - Sae-Lim, Pirunrat; Mamoodben, Nolear; Phonlamueang, Siriporn; Noochoochat, Atittaya; Khongpuckde, Sonsawan (PKRU SciTech Journal, 2024)
The purpose of this study was to compare the physical properties, chemical properties, and stabilities of the extracts obtained from fresh and dried herb ingredients used in Thai herbal compress balls. The extracts were obtained using coconut oil and ethanol as solvents through the microwave-assisted extraction. The results indicated that dried herbs extracted with coconut oil and ethanol exhibited a more greenish-brown color, higher concentration, viscosity, and pH compared to fresh herbs extracted with both solvents. Moreover, they also exhibited a better aroma. Additionally, when comparing the stability, overall physical and chemical properties, it was observed that the dried herbs extracted with ethanol maintained stability under all conditions. There were no changes observed in the physical characteristics, viscosity, and acidity. These findings suggest that the dried herbs extracted with ethanol are suitable for further development into herbal products for external use in the future.